Transcriptional Changes In Response To Single And Combine Inoculation Of Mycorrhiza And Ganoderma In Oil Palm (Elaeis Guineensis Jacq.) Roots - Tee, Sue Sean (2009)

(untitled)
Mycorrhiza is a symbiotic fungus that aids in nutrient uptake, enhances root development and promotes plant growth in most of the vascular flowering plants. Under natural conditions, oil palm is often colonized by arbuscular mycorrhizal (AM) fungi. AM was also proposed to mitigate Ganoderma infection, which leads to basal stem rot (BSR) disease in oil palm. In this study, cDNA microarray approach was used to examine the transcript profile of oil palm roots during the development of AM symbiosis and upon Ganoderma infection. Besides, the role of AM as a biocontrol agent against BSR disease was also investigated. The analysis of microarray results using LIMMA (Linear Model for Microarray Analysis) revealed that different sets of genes were expressed upon different interactions. A total of 183 genes, 123 genes and 391 genes were up- or down-regulated in oil palm in response to mycorrhizal inoculation, Ganoderma infection and Ganoderma-mycorrhizal inoculation, respectively. Among the differentially expressed genes, defense and stress related genes formed the largest category in all three treatments, such as putative beta 1,3-glucanase, early methionine labeled polypeptide, metallothionein-like protein and type 2 ribosome-inactivating protein cinnamomin III precursor. These transcripts were regulated differently in different experimental conditions. Isoflavone reductase homolog was found to be differentially expressed in Ganoderma infected root, implying the involvement of isoflavonoid phytoalexin in oil palm defense system against BSR disease. The results also showed that different types of protein kinase and calmodulin were differentially expressed in mycorrhizal symbiosis and Ganoderma infection. The WRKY and bHLH transcription factors were among the transcription factors which have been identified in oil palm mycorrhizal and Ganoderma interaction studies. In addition, a number of cell wall related proteins such as plasma membrane proteins were differentially expressed in mycorrhizal and Ganoderma-mycorrhizal treatment inferring the importance of cell wall proteins during mycorrhizal inoculation. Although the mycorrhization of oil palm was unable to suppress Ganoderma infection, the transcription profiles of oil palm Ganoderma-mycorrhizal interaction showed that many defense related transcripts were induced indicating that mycorrhiza might induce systemic resistance of oil palm against Ganoderma infection. In conclusion, the findings of this study have provided new insights into the molecular events that happened during symbiotic and pathogenic associations of fungi with oil palms.